Assessing Convergent and Discriminant Validity of the Motivation Construct for the Technology Integration Education (TIE) Model - Engellant, Kevin A.; Holland, Denise D.; Piper, Randy T. (Journal of Higher Education Theory and Practice, 2019)
Motivation researchers have given high priority to the nomological validity of the motivation construct by creating diverse models such as the technology integration education (TIE) model as part of the technological, pedagogical, and content knowledge (TPACK) research agenda. However, researchers have not given equally high priority to convergent validity and discriminant validity. This study incorporated the multitrait-multimethod (MTMM) matrix to discover evidence of convergent validity and discriminant validity for self-determination theory motivation and social cognitive theory motivation. The researchers found limited evidence of convergent validity and discriminant validity for the motivation construct.